SOFI Simulation Tool: A Software Package for Simulating and Testing Super-Resolution Optical Fluctuation Imaging - Girsault, Arik; Lukes, Tomas; Sharipov, Azat; Geissbuehler, Stefan; Leutenegger, Marcel; Vandenberg, Wim; Dedecker, Peter; Hofkens, Johan; Lasser, Theo (PLoS One, 2016)
Super-resolution optical fluctuation imaging (SOFI) allows one to perform sub-diffraction fluorescence microscopy of living cells. By analyzing the acquired image sequence with an advanced correlation method, i.e. a high-order cross-cumulant analysis, super-resolution in all three spatial dimensions can be achieved. Here we introduce a software tool for a simple qualitative comparison of SOFI images under simulated conditions considering parameters of the microscope setup and essential properties of the biological sample. This tool incorporates SOFI and STORM algorithms, displays and describes the SOFI image processing steps in a tutorial-like fashion. Fast testing of various parameters simplifies the parameter optimization prior to experimental work. The performance of the simulation tool is demonstrated by comparing simulated results with experimentally acquired data.
Keywords: algoritmy; HeLa Cells; Software; software; Humans; lidé; HeLa buňky; Microscopy, Fluorescence; počítačové zpracování obrazu; Image Processing, Computer-Assisted; fluorescenční mikroskopie; Algorithms